ANALYSIS OF GUEST SERVICE ASSISTANT SERVICE QUALITY FOR GUESTS’ SATISFACTION AT THE ONE LEGIAN HOTEL - I Nyoman Esa Arimbawa; I Gusti Agung Bagus Mataram; I Ketut Budarma (Politeknik Negeri Bali, 2019)
This research examines the role of the Guest Service Assistant known as receptionist, as one of the most important service agents of The ONE Legian Hotel. The purpose of this research is to analyze if there is a negative gap between the guests’ perception and expectation to the Guest Service Assistant service quality of The ONE Legian Hotel. The total of samples involved is 120 respondents by incidental sampling method. The data collection method is questionnaire which has been tested its validity and reliability, and using Likert scale. Data analysis technique used is the SERVQUAL Method. The overall research findings show that there is no negative gap between the guests’ perception and expectation which means that the overall guest perceives the service quality of the receptionist at The ONE Legian Hotel positively. However, dimension-by-dimension analysis found that the Guest Service Assistant of The ONE Legian Hotel could improve more its performance especially for the reliability service quality dimension for maximizing the guests’ satisfaction.